2014
DOI: 10.1038/sc.2014.153
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Injury: Scenario in an Indian State

Abstract: Epidemiological factors of SCI in Indian scenario are different from western countries with major cause being fall. The low socio-economic status and younger age group had a major financial, social and psychological impact as majority of the patients were the primary earning members of the family. Therefore, measures should be taken to reduce the incidence of SCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
48
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 19 publications
5
48
2
3
Order By: Relevance
“…The male/female ratio was 4.33:1 in the present research, which was similar to other studies, 4,11,[15][16][17] particularly similar to a systematic review. 7 Similar to other regions, 10,11 in Chongqing, the majority of women were also employed in occupations with low risk of TSCI, while high physical-risk behaviors are primarily performed by men.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The male/female ratio was 4.33:1 in the present research, which was similar to other studies, 4,11,[15][16][17] particularly similar to a systematic review. 7 Similar to other regions, 10,11 in Chongqing, the majority of women were also employed in occupations with low risk of TSCI, while high physical-risk behaviors are primarily performed by men.…”
Section: Discussionsupporting
confidence: 93%
“…The results of occupational characteristics in the current study were the same as previously reported in Tianjin, 11 Anhui, 10 and India. 15 In our results, the percentages of peasants and laborers were 31.9% (177) and 23.6% (131), respectively. This fact was mainly because the educational background of these patients was relatively low, thus limiting them to manual work and increased vulnerability to TSCI, which may explain the increased burden of TSCI in this occupational group.…”
Section: Discussionmentioning
confidence: 84%
“…15 A study done by Mathur et al in India found that 53% patients had a history of fall. 16 Assaults, including firearm injuries are the third most common cause responsible for TSCI. A study done in South America showed 16.8% cases of firearm injuries, whereas a Brazilian study showed 42% cases, while it was 25% in a study from Turkey and 21% from Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Prospective data was collected during 2016, although this is not yet complete, pending the discharge of some patients from rehabilitation. Prospective [4-6] and retrospective [7-11] studies are both widely published, all useful in the country or context in which they were planned. While awaiting completion of the collection and analysis of prospective data, the conclusion from a feasibility exercise was that a retrospective study would be useful to analyse trends over successive years, to assist with health services planning [12].…”
Section: Introductionmentioning
confidence: 99%